Rutas gastronómicas y su relación con la gastronomía tradicional de la ciudad de Latacunga, provincia de Cotopaxi. - Puertas Jiménez, Juan Sebastián (2025)
The present research, titled "Gastronomic Routes and Their Relationship with Traditional Gastronomy in the City of Latacunga, Cotopaxi Province," seeks to explore the connection between culinary tourism and traditional local cuisine. The study acknowledges the valuable contributions of the staff from the Tourism Department of the Municipality of Latacunga, as well as the proprietors of gastronomic establishments that offer traditional culinary services within the city. A total of 13 municipal tourism personnel and 30 traditional gastronomy establishments were selected to participate in the study as determined through the application of surveys. This research is descriptive and exploratory in nature, employing a non-experimental, cross-sectional design. The data collection method consisted of a structured questionnaire utilizing a Likert-type scale with the following categories: Not Important, Slightly Important, Moderately Important, Important, and Very Important. The data gathered were tabulated and analyzed using Microsoft Excel and IBM SPSS Statistics (version 23). These tools facilitated hypothesis testing to examine the relationships between the study’s variables and their respective dimensions. The research concludes with a proposal centered on gastronomic routes, confirming their significant relationship with traditional gastronomy in the city of Latacunga. The findings contribute to a clear, rigorous, and well-substantiated academic investigation. Keywords: Gastronomic routes, traditional gastronomy, tourist product, local culture, economic development.